2007
DOI: 10.1074/jbc.m608318200
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-inducible Expression of a Natural cis-Antisense Transcript Inhibits Endothelial Nitric-oxide Synthase

Abstract: The destabilization of endothelial nitric-oxide synthase (eNOS) mRNA in hypoxic endothelial cells may be important in the etiology of vascular diseases, such as pulmonary hypertension. Recently, an overlapping antisense transcript to eNOS/NOS3 was implicated in the post-transcriptional regulation of eNOS. We demonstrate here that expression of sONE, also known as eNOS antisense (NOS3AS) or autophagy 9-like 2 (APG9L2), is robustly induced by hypoxia or functional deficiency of von Hippel-Lindau protein. sONE is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
122
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 133 publications
(129 citation statements)
references
References 75 publications
7
122
0
Order By: Relevance
“…Importantly, this primer set also amplifies pre-mRNA generated from the sONE/NOS3AS gene, which is transcribed in a tail-to-tail fashion to eNOS on the opposite DNA strand. We have recently demonstrated that NOS3AS transcription is maintained during hypoxic exposure of endothelial cells (1-6 h) (34).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Importantly, this primer set also amplifies pre-mRNA generated from the sONE/NOS3AS gene, which is transcribed in a tail-to-tail fashion to eNOS on the opposite DNA strand. We have recently demonstrated that NOS3AS transcription is maintained during hypoxic exposure of endothelial cells (1-6 h) (34).…”
Section: Resultsmentioning
confidence: 98%
“…Hypoxia Down-regulates eNOS Transcription-Prior studies by us and others have investigated hypoxia-mediated decreases in eNOS expression using in vitro approaches (4,34,35). We have also previously determined the effect of hypoxic exposure on the transcriptional activity of the chromatin-integrated eNOS promoter in vivo by exposing eNOS insertional promoter/reporter transgenic mice to hypoxia (8%, 48 h) and assessing reporter expression in the endothelial cells of the renal papilla (36).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Total RNA extraction and real-time PCR was performed as described (8). Specific primers are indicated in Table S2 and Table S3.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, hypoxia leads to decreases in endothelial NOS (eNOS) mRNA and increases nNOS mRNA expression in vascular endothelium and smooth muscle cells, respectively (8,9). Studies have demonstrated that acute anemia causes tissue hypoxia and an increase in hypoxia-inducible factor-alpha (HIF-α) and neuronal NOS (nNOS) protein levels, especially in the brain (10,11).…”
mentioning
confidence: 99%